The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1155/2011/738301
|View full text |Cite
|
Sign up to set email alerts
|

Effector Caspases and Leukemia

Abstract: Caspases, a family of aspartate-specific cysteine proteases, play a major role in apoptosis and a variety of physiological and pathological processes. Fourteen mammalian caspases have been identified and can be divided into two groups: inflammatory caspases and apoptotic caspases. Based on the structure and function, the apoptotic caspases are further grouped into initiator/apical caspases (caspase-2, -8, -9, and -10) and effector/executioner caspases (caspase-3, -6, and -7). In this paper, we discuss what we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 102 publications
0
18
0
1
Order By: Relevance
“…Caspase-3 is a key protease activated during the early stages of apoptosis and, like other members of the caspase family, is synthesized as an inactive proenzyme that is processed in cells undergoing apoptosis by self-proteolysis and/or cleavage by another protease such as caspase 8 or 9 (Patel et al 1996). Caspase-7 is highly similar in structure (58%) and substrate-specificity to caspase-3, and caspases-3/7 are effector/executioner caspases (Lu and Chen 2011). Caspases 8 and 9 are also synthesized as inactive pro-caspases that are processed in cells undergoing apoptosis by self-proteolysis and/or cleavage by another protease (Patel et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-3 is a key protease activated during the early stages of apoptosis and, like other members of the caspase family, is synthesized as an inactive proenzyme that is processed in cells undergoing apoptosis by self-proteolysis and/or cleavage by another protease such as caspase 8 or 9 (Patel et al 1996). Caspase-7 is highly similar in structure (58%) and substrate-specificity to caspase-3, and caspases-3/7 are effector/executioner caspases (Lu and Chen 2011). Caspases 8 and 9 are also synthesized as inactive pro-caspases that are processed in cells undergoing apoptosis by self-proteolysis and/or cleavage by another protease (Patel et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Таким образом, можно предположить, что ме-ханизм действия реамберина связан с подавлением внеш-нерецепторного и р53-зависимого пути. Повышение ин-тенсивности синтеза каспазы-3 при введении Реамберина при нормальном уровне апоптоза может указывать на ее неапоптотическую функцию, что показано и другими авторами [11]. Примечание.…”
Section: результаты и обсуждениеunclassified
“…[10][11][12][13] Caspase-3 has been found to be essential for normal brain development in some genetic mouse strains 14 ; however, Caspase-3-deficient mice are viable and fertile in the C57BL/6 strain with no apparent defects in brain pathology. 15,16 Caspase-3 has been shown to play important roles at multiple steps in embryonic stem cells and HSCs, affecting self-renewal and differentiation. [17][18][19] In the hematopoietic system, loss of Caspase-3 leads to accelerated proliferation and impaired differentiation of bone marrow cells.…”
Section: Introductionmentioning
confidence: 99%
“…24 We and others have shown that AE is a direct substrate of Caspase-3 and the cleavage sites are TMPD188 and LLLD368. 15,25,26 Moreover, a truncated AE protein (DAE), generated by cleavage of AE at Asp188, worked as a dominant-negative protein by interacting with AE and interfering with its oncogenic functions. 27,28 Together, these data suggest that AE may accumulate in a Caspase-3 compromised background and thereby accelerate leukemogenesis.…”
Section: Introductionmentioning
confidence: 99%